Mobility and reliefs for traveling expenses to work - Matthias Wrede (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 1999)
This paper proposes the question whether or not traveling expenses to work should be deductible from the income tax base. In order to answer this question, a simple model of (im-) perfect household and worker mobility is employed. The focus of the analysis is on the efficient use of land and the efficient allocation of people and labor in a multi-region framework. The paper shows that deductibility is inefficient only if households are perfectly mobile and if households cannot choose their place of work. If the region of work is not exogenously fixed, traveling expenses to work should be deductible at more than one hundred percent, even if households choose simultaneously the place of work and the region of residence, and even if tax rates are not standardized within the federation.
Keywords: H21; H24; J61; 330; income taxation; reliefs; household mobility; labor mobility; raveling expenses to work; optimum taxation; Kosten; Steuerbegünstigung; Lohnsteuer; Optimale Besteuerung; Arbeitsmobilität; Wohnungswechsel; Standorttheorie; Theorie; Pendelverkehr